Identification of significant SNPs for yield-related salt tolerant traits in rice through genome-wide association analysis: SNPs for yield-related salt tolerant in rice via GWAS - Era, Farzana Mustafa; Raihan, Mohammad Sharif; Jahan, Nusrat; Pandey, Saurabh; Alalawy, Adel I.; Al‑Duais, Mohammed Ali; Alharbi, Basmah M.; Alqurashi, Mohammed; Erden, Zeki; Toprak , Çağdaş Can; Islam, A. K. M. Aminul (Cellular and Molecular Biology, 2025)
Rice salt tolerance is highly anticipated to meet global demand in response to decreasing farmland and soil salinization. Therefore, dissecting the genetic loci controlling salt tolerance in rice for improving productivity is of utmost importance. Here, we evaluated six salt-tolerance-related traits of a biparental mapping population comprising 280 F2 rice individuals (Oryza sativa L.) at the seedling and reproductive stages. We performed a genome-wide association study (GWAS) to identify marker-trait associations under artificially induced salt stress using the 1K RICA chip (Agriplex Genomics, Cedar Avenue, Suite 250, Cleveland, 011444106, USA). We have identified 8 single nucleotide polymorphisms (SNPs) representing eight genomic regions on chromosomes 5, 8, 9, and 10. These were significantly associated with the six salt-tolerance-related traits, no. of tillers per plant (TPP), effective tillers per plant (ETP), spikelet fertility percentage (SFP), field grain number (FGN), grain length breadth ratio (LBR) and thousand-grain weight (TGW). FGN has two significant SNPs (SNP0758 and SNP0759) on Chromosome 9, whereas SFP on chromosomes 8 and 12 (SNP1127 and SNP0966, respectively). Similarly, for TPP (SNP0796), a significant SNP was detected on chromosome 10, and for ETP (SNP0414) on chromosome 5. Two significant SNPs were found in chromosome 12 for LBR (SNP0920) and TGW (SNP0976). Based on all loci, we screened 3 possible candidate genes in chromosomes 8, 9, and 12 between the genomic region of SNP0920 and SNP1127 under salt stress. Interestingly, these genes were involved in protein coding, none of which was previously reported as being involved in plant salt tolerance. Further, the genetic relationship between the mapping population and population structure was classified by STRUCTURE v 2.3. Genotypes with ≥ 80% of shared ancestry were explained into two major clusters (I and II), and < 80% of shared ancestry were categorized as admixtures. An unrooted alpha was developed by TASSEL 5.0, dividing the genotypes into three major groups where 97 individuals were in Cluster 1, cluster 2 consisted of 93 individuals, and the remaining Cluster 3 included 90 individuals. A kinship matrix developed from 860 SNPs indicated group formation and more substantial relatedness among the genotypes with a red zone. Our findings provide valuable information for enhancing the understanding of complicated salt tolerance mechanisms in rice seedlings and the identified candidates potentially used for breeding salt-tolerant genotypes.